TRANSFORMATIONAL LEADERSHIP AND ITS EFFECT ON EMPLOYEE PSYCHOLOGICAL WELL-BEING IN SELECTED DELTA STATE BROADCAST STATIONS - Oyovwevotu V. Erakpotobo; Ugo C. Okolie; Ndubuisi J. Memeh (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Main Objective: This study examined the effect of transformational leadership on the employee psychological well-being in selected Delta State broadcasting stations. Background Problems: Managers and governments across the globe are concerned about employee psychological health. Organizations in Nigeria have paid little attention to their employees' psychological well-being, and the majority of top executives in the broadcasting industry are unaware of the impact that transformational leadership has on the workforce's psychological well-being. The goal of this research is to investigate transformational leadership and its effect on employee psychological well-being in selected sample of Delta State broadcasting stations. Novelty: Transformational leadership is an effective type of leadership that encourages workers to perform better by increasing their levels of competence and self-reinforcement. Research Methods: The cross-sectional research design approach was used in this study. The participants in this study included 173 management and non-management employees from the Nigerian Television Authority in Asaba (47) and the Delta State Broadcasting Services in Asaba (69) and Warri (57) respectively. Using the SPSS software version 23.0, data was analyzed using linear regression. Findings/Results: According to the findings, transformational leadership had a significant and positive effect on employee psychological well-being. Conclusion: Transformational leaders work toward a common goal with followers, often self-sacrificing, prioritize employees, and develop them.